Corollary Impact of Corona on The Medical Tourism Industry: With Special Focus on India - Jyothsna P. KUNAPAREDDY (Communications of International Proceedings, 2020)
Medical Tourism is a glamorous industry witnessing a tremendous growth. The global medical tourism market was valued at USD 16,761 million in 2018, USD 44.8 billion in 2019 and it is expected to reach USD 27,247.6 million by 2024. The Indian medical tourism market is expected to touch the $9 billion by 2020, according to Federation of Indian Chambers of Commerce and Industry (FICCI) and Ernst & Young. Since Feb 2020, the whole world is tumbled down by the Pandemic-Covid 19, Corona catastrophe. The Paper aims at assessing the impact of Corona pandemic on Indian Medical Tourism market, evaluates the impact of Corona pandemic on the industries directly or indirectly related to medical tourism industry. The manuscript is developed based on extensive literature review. The paper unravels the future scenario of the industries which are directly or indirectly related to Indian medical tourism industry. The paper alerts Indian business entrepreneurs and prepares them for the upcoming scenario, thereby helps them to make better strategies for the recoup.
Keywords: Medical Tourism; Corona; Pandemic.